Electric Vehicle Lithium Ion Batteries Thermal Management - Gaoussou Hadia Fofana; You Tong Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The lithium ion batteries, thanks to their high densities and high power, became promotes element for hybrid-electric and plug-in electric vehicles. Thermal management of lithium ion battery is important for many reasons, including thermal runaway, performance and maintains a constant temperature during the operating, security, lifecycle. However, in a battery pack, the batteries are stacked against each other without cooling surfaces except the outer surface of the package and the cell in the center of pack are exposed to overheating and thermal runaway. After several recent researches, it has been proved that lithium ion batteries are currently confronts a problem of temperature rise during their operation discharge, which affects the batteries performance, efficiency and reduces the life of lithium ion batteries.  However, this work is set to access the three dimensional analytical modeling based on Green’s Function technique to study the thermal behavior of lithium ion battery during discharge with different discharge rates (0.3C, C/2, 1C, 2C) and strategies natural convection cooling on the surface of the battery is performed. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4026